Ketahanan terhadap Rayap, Sifat Kimia, dan Warna Kayu Jati dari Hutan Rakyat di Kulon Progo (Termite Resistance, Chemical, and Colour Properties of Teak Wood from Community Forests of Kulon Progo) - Ganis Lukmandaru; Mauidlotul Hasanah; Nuridha I Retnaningrum (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
woods from community forests are harvested at young stage with high sapwood proportion. The aim of this study was to measure the variation of termite resistance, chemical, and colour properties for teak wood from two site (Temon dan Kalibawang) with different ecological conditions in Kulon Progo and it is compared to mature woods from Perhutani plantation of FMU Madiun. The results showed that wood from community forests and Madiun were not statistically different with regard to the attacks of dry-wood Cryptotermes cynocephalus termites. Against subterranean Cryptotermes cynocephalus termites, wood samples from Kulon Progo were more susceptible particularly the sapwood parts although samples from Kalibawang showed termite resistance similar to termite resistance of Madiun samples in the heartwood region. The gravimetric determination of ethanol-toluene extractive and lignin content resulted no significant effect of site and radial direction factors. Based on colour properties by CIELab system measurements, samples of Kulon Progo community forests exhibited a lighter colour than those of Madiun. A significant correlation was measured between mass loss and extractive content. Mass loss due to subterranean termite attacks in the heartwood part significantly correlated to colour properties (lightness and redness indices).Keywords: colour properties, community forest, extractive content, Tectona grandis, termite resistance